I - Object: Intimate Technologies as 'Reference Groups' in the Construction of Identities. - van den Berg, Bibi (Techné: Research in Philosophy & Technology)
In this article, I will investigate the ways in which Ambient Intelligence, the technological paradigm of the near future proposed by the European Union and the electronics multinational Philips, will affect the ways in which individuals construct and express their identities. The Ambient Intelligence vision predicts a world in which technologies will deliver personalized services in a proactive (rather than a responsive or interactive) fashion. I argue that this brings about a change in the way we interact with these technologies, which in turn has an effect on the way we construct and express identities in relation to such technologies. In a world of Ambient Intelligence, I will argue in this article, technological artifacts may come to function as 'reference collectivities', comparable to human reference groups. Due to their proactivity, their level of autonomy and self-reliance and our personalized interactions with them, these technologies will come to function as 'others', rather than as 'quasi-others'.